1957
DOI: 10.1085/jgp.40.5.753
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sodium, Potassium, and Chloride in Amphibian Muscle

Abstract: In a previous publication (28) it was shown that the cells of the sartorius muscle of the toad Bufo marinus were able to maintain their internal K + at an absolute level despite great fluctuations (0 to 25 m.eq. per liter) of the external K +. When the external level was raised to 50 m.eq. per liter there was an intracellular increase amounting to about 17 per cent of the control level in normal Ringer. This is in contrast to the capacity of the cell to maintain an absolute ratio Na+ou~/Na+m of approximately 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1959
1959
1975
1975

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The absolute volumes as calculated from our data and as predicted of course agree at normal osmotic pressure since they were taken in both cases to be the same, namely 13 % of cell volume. At 3x5 x N osmotic pressure the predicted volume is (Steinbach, 1947;Simon, Shaw, Bennett & Muller, 1957) (Frazini-Armstrong & Porter, 1964;Huxley, 1964;Page, 1964;Birks, 1965) and it appears unlikely that any element of the sarcoplasmic reticulum itself is open to extracellular fluid at the sarcolemma. Thus the most likely site for extracellular fluid to gain access to the sarcoplasmic reticulum is at the region of contact between the transverse tubules and the triad sacs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute volumes as calculated from our data and as predicted of course agree at normal osmotic pressure since they were taken in both cases to be the same, namely 13 % of cell volume. At 3x5 x N osmotic pressure the predicted volume is (Steinbach, 1947;Simon, Shaw, Bennett & Muller, 1957) (Frazini-Armstrong & Porter, 1964;Huxley, 1964;Page, 1964;Birks, 1965) and it appears unlikely that any element of the sarcoplasmic reticulum itself is open to extracellular fluid at the sarcolemma. Thus the most likely site for extracellular fluid to gain access to the sarcoplasmic reticulum is at the region of contact between the transverse tubules and the triad sacs.…”
Section: Discussionmentioning
confidence: 99%
“…It is of considerable interest with regard to this hypothesis that studies on the distribution of electrolytes in frog skeletal muscle have consistently revealed a discrepancy between the actual measured intracellular ion concentrations and the concentrations which are predicted for muscle by the Donnan equilibrium. To explain this discrepancy a number of workers (Steinbach, 1947;Simon, Shaw, Bennett & Muller, 1957) have postulated the existence of a small intra-fibre compartment accessible to all extracellular ions. Harris (1963) on the basis of studies on the distribution of muscle chloride, calculated that for the Donnan equilibrium to hold, this space must contain 15 % of the total cell water (about 12 % of cell volume), a figure in remarkable agreement with the volume of the sarcoplasmic reticulum as measured by Peachey (1965), and considered as a possible location for this space by Harris.…”
Section: Discussionmentioning
confidence: 99%
“…The initial loss of extracellular Na+ would reduce this gradient, which would tend to be restored 'by a later loss of intracellular Na+ (Simon, Shaw, Bennett & Muller, 1957). Some evidence for this hypothesis is derived from the observation that the restitution of extracellular Na+ brought about an initial increase in the ACh response to greater than normal levels; one would expect the Na+ gradient to be temporarily increased.…”
Section: Sodium Substitution With Sucrosementioning
confidence: 99%
“…It is possible that the partial restoration of tension which was occasionally seen after prolonged exposure to low Na+ or Na+-free solution maybe related to the partial dependence of the ACh contraction on the Na+ gradient across the membrane. The initial loss of extracellular Na+ would reduce this gradient, which would tend to be restored 'by a later loss of intracellular Na+ (Simon, Shaw, Bennett & Muller, 1957). Some evidence for this hypothesis is derived from the observation that the restitution of extracellular Na+ brought about an initial increase in the ACh response to Effect of Na+ depletion on the ACh contraction of denervated diaphragm.…”
Section: Sodium Substitution With Sucrosementioning
confidence: 99%
“…This phenomenon did not happen in all muscles, but tended to take place in muscles with low resting potentials. One factor for this irregularity may be the great variability of Na content in the muscle (Simon, Shaw, Bennett & Muller, 1957). The time course of the reversed e.p.p.…”
mentioning
confidence: 99%